MOTIVATING LABOUR ACTIVITY OF THE ACULTY - Alexander V. Titovskiy; Gennadiy B. Kondrakov; Tatyana I. Makarenkova; Mikhail V. Alaev (Вестник Российского экономического университета имени Г. В. Плеханова)
Today the efficiency and rating of higher education institutions are based on quantitative criteria set by the Ministry of Education and Science. The final indicators of the division work are formed by labour activity of lecturers, who make up the intellectual potential of the department. The article puts forward a model of advanced methods of motivating lecturers' labour activity illustrated by distribution of the quarter bonus. This project can serve as a basis for the effective contract and set clear labour requirements for employees applying to the contest. By analyzing the results we can see the high efficiency of using the matrix of motivating the faculty work to improve the rating of the department.